Effect of molar ratio (M²⁺/M³⁺) of Mg-Al-NO₃-layered double hydroxide on dye adsorption / Asiah Mohd. Shafiee - Mohd. Shafiee, Asiah (Faculty of Applied Sciences, 2010)
Layered double hydroxide (LDH) is lamellar mixed hydroxide containing positively charged main layers and undergoing anion exchange chemistry. In this study, MgAl layered hydroxides (LDHs) have been prepared with NO₃⁻ interlayer anions and with Mg/Al ratio 2, 3 and 4. The LDHs were characterized by X-Ray Diffractometer (X-RD), Fourier Transform Infrared (FT-IR) and Field Emission Scanning Electron Microscopy (FESEM). The X-RD patterns for the LDHs show intense and sharp peaks of d-spacing at about 8.00 Å - 8.90 Å and interlayer spacing peaks approximately 4.00 Å - 4.50 Å. After adsorption, the basal spacing of the LDHs decreases due to the small molecular size of anionic dyes and mostly, the adsorption occurs on the external surface of the LDHs. The FT-IR spectrum of the LDHs were identified and the adsorption has occurred onto the LDHs as the functional groups of dyes appear in the FT-IR spectrum. While, from the FESEM analysis, it shows that the LDHs has well-defined plate-shaped crystals. Moreover, the different ratio of LDHs were investigated by comparing their adsoption efficiency on different type of dyes which are Reactive Red 120 (RR120), Reactive Orange 16 (R016) and Reactive Black 5 (RB5). And, the results obtained shows that LDH of ratio 4 has the best adsorption efficieny, followed by LDH of ratio 3 and then ratio 2.